Deduction of two-dimensional blood flow vector by dual angle diverging waves from a cardiac sector probe. (20th April 2018) - Maeda, Moe; Nagaoka, Ryo; Ikeda, Hayato; Yaegashi, So; Saijo, Yoshifumi
Abstract: Color Doppler method is widely used for noninvasive diagnosis of heart diseases. However, the method can measure one-dimensional (1D) blood flow velocity only along an ultrasonic beam. In this study, diverging waves with two different angles were irradiated from a cardiac sector probe to estimate a two-dimensional (2D) blood flow vector from each velocity measured with the angles. The feasibility of the proposed method was evaluated in experiments using flow poly(vinyl alcohol) (PVA) gel phantoms. The 2D velocity vectors obtained with the proposed method were compared with the flow vectors obtained with the particle image velocimetry (PIV) method. Root mean square errors of the axial and lateral components were 11.3 and 29.5 mm/s, respectively. The proposed method was also applied to echo data from the left ventricle of the heart. The inflow from the mitral valve in diastole and the ejection flow concentrating in the aorta in systole were visualized.